Analisis Kinerja Dan Manajemen Lalu Lintas pada Bundaran ITS dan Bundaran Mulyosari Kota Surabaya - Satoinong, Laif; Mardijono, Mardijono; Donny, Shofwan; Ray, Norman; Budi, Leonardus Setia (Universitas Dr. Soetomo, 2019)
The aim of this thesis is solving the problem of jamming it happen at ITS roundabout and Mulyosari. In research and management of data, and theory which use is MKJI of 1997. The solving of this thesis needed as traffic light data on existing situation. Then, there are survey data at ITC roundabout and Mulyosari roundabout on 2018.Â The function of this survey is to know about the real condition performance both of Circles.Â Finally, both of circles are not effective (Jamming traffic light). Forward, predictions of performance traffic light in 5 years later until 2022 from 2018, finally more not effective. In this thesis gives the solution in case should use the traffic light. Finally, the solution as counting, that both of roundabout about traffic light become effective.